Healthy Living Community Movement (GERMAS) Through Aerobic Gymnastics And Healthy Walks In Commemorating The 106th Milad Muhammadiyah - Ramli Ramli; Hairudin La Patilaiya; Amalan Tomia; Monissa A.Hi Djafar (International Journal Of Community Service, 2022)
The Healthy Living Community Movement (GERMAS) is a systematic and planned action carried out jointly by all components of the nation with awareness, willingness and ability to behave in a healthy manner to improve the quality of life. One of GERMAS activities is Improving Physical Activity, therefore on the 106th Milad Muhammadiyah with the theme Ta'awun for the Country, the North Maluku Muhammadiyah Regional Leadership (PWM Malut) held Aerobic Gymnastics and Healthy Walks as an effort to prevent disease (heart, lung, stroke, diabetes, etc.) and as an effort to improve public health. Aerobic Gymnastics was held on October 26, 2018 at the UMM campus, while the Healthy Walk was also held on November 24, 2018 with a meeting point at the Landmark (Muhajirin Village) and a healthy walk at the Sultan Mosque. Ternate (Soa Sio Village) as well as the finishing place at the Ternate Al-Munawwar Grand Mosque. With this GERMAS activity, it is hoped that a healthy lifestyle will be formed, especially for North Maluku Muhammadiyah residents and society in general. Therefore, in this community service journal, the author also includes the Yutube link for aerobic exercise (Low Impact & High Impact, Tobelo Gymnastics and Diabetes Gymnastics) so that readers can immediately practice aerobic exercise as an effort to prevent disease and improve health from various diseases.